The applicability of the policy transfer framework to understanding higher education reforms in Kazakhstan: the case of the Bologna process - Ilyassova-Schoenfeld, Aray (2017)
This thesis examines higher education reforms in Kazakhstan from 1991 to 2016, and uses the policy transfer framework to analyse the case of the Bologna Process in this developing post-communist country. Following the collapse of the Soviet Union, newly independent Kazakhstan aimed to shift from a resource-based economy to an industrial innovation-based economy. Modeled on Western countries’ training to develop its professionals and competitive experts, Kazakhstan aimed to reform its education system to increase the quality and competitiveness of its higher education, and to enhance the recognition of local research and faculties. In order to integrate into the international educational space, and to connect with the education systems of the USA and Europe, Kazakhstan initiated its entrance into the Bologna Process which is an intergovernmental policy for the development of higher education in Europe. Policy transfer is used as an explanatory theory. It is a useful theoretical approach to understand post-communist countries in transition because it provides a critical analytical tool with which to understand significant changes of direction. The policy transfer was used to explain why Kazakhstan signed the Bologna Process. This research used 41 semi-structured interviews with international and national actors engaged in the Bologna Process to understand the relationship between European, national and institutional levels. The broad notion of policy transfer accommodates various tools for conducting empirical research, including the policy cycle, multi-level, ideational and process-centred approaches. By applying a theoretical framework that was so far predominantly used in Western countries, this thesis contributed to the academic literature on post-communist countries. This thesis considered four different, but connected concepts: policy learning, international policy transfer, lesson-drawing and path dependency. This research argues that the policy transfer process in higher education mainly occurs through learning. Not only reforms or policy were transferred, but policy ideas and knowledge were transferred too. Lesson-drawing and lesson learning occurred in the example of countries where higher education and science are advanced and well-developed, such as the USA and some European countries. In changing its education system and becoming integrated into the European Higher Education Area, Kazakhstan used lesson-drawing, policy learning and international policy processes. International policy transfer provides a model which is applicable to post-communist countries with different political, ideological, economic, social and cultural backgrounds. Many transfers involve a combination of voluntary and coercive elements. Policy makers sought ‘new’ knowledge and policy ideas from other systems that were compatible with their ideological and cultural perspectives. In Kazakhstan, the transfer was voluntary, and could be characterised as lesson-drawing. At the same time, the country faced a need to change its social and economic situation due to the collapse of the country. All of these changes drove policy makers to engage in policy transfer in order to cope with external pressures such as globalisation and international integration. Bottom-up initiatives were launched where universities persuaded the Ministry of Education to adopt decisions at the national level. This thesis argues that national and institutional levels were equally involved in the process of decision-making in Kazakhstan. Kazakhstan inherited the Soviet system of higher education. Historically and culturally, the country is not associated with Western Europe, and both history and culture have to be taken into account in the process of policy transfer. This research argues that path dependency is one of the dimensions of policy transfer, and that historical paths of a country should be considered before transferring policy from abroad. Understanding of path dependency should guide evaluation of all possible constraints that might limit the policy transfer process from the West to developing countries This thesis developed the concept of policy transfer by considering path dependency as a key factor in explaining policy reform, making an original and distinctive contribution to the knowledge of policy making and, more broadly, academic literature, in Kazakhstan and internationally.